Spark plasma sintering of TiB2-based ceramics with Ti3AlC2. Issue 9 (1st May 2021) - Nayebi, Behzad; Shahedi Asl, Mehdi; Akhlaghi, Maryam; Ahmadi, Zohre; Tayebifard, Seyed Ali; Salahi, Esmaeil; Shokouhimehr, Mohammadreza; Mohammadi, Mohsen
Abstract: A TiB2 –Ti3 AlC2 ceramic was manufactured by spark plasma sintering at 1900 °C temperature for 7 min soaking time under 30 MPa biaxial pressure. The role of Ti3 AlC2 additive on the microstructure development, densification behavior, phase evolution, and hardness of the ceramic composite were studied. The phase characterization and microstructural investigations unveiled that the Ti3 AlC2 MAX phase decomposes at the initial stages of the sintering. The in-situ formed phases, induced by the decomposition of Ti3 AlC2 additive, were identified and scrutinized by XRD and FESEM/EDS techniques as well as thermodynamics principles. The sintered TiB2 –Ti3 AlC2 ceramic approached a near full density of ~99% and a hardness of ~28 GPa. The densification mechanism and sintering phenomena were discussed and graphically illustrated.